2021
DOI: 10.1002/adfm.202100034
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing Oxygen Reduction Activity and Cr Tolerance of Solid Oxide Fuel Cell Cathodes by a Multiphase Catalyst Coating

Abstract: Intermediate temperature solid oxide fuel cells (IT‐SOFCs) are cost‐effective and efficient energy conversion systems. The sluggish oxygen reduction reaction (ORR) and the degradation of cathodes are critical challenges to the commercialization of IT‐SOFCs. Here, a highly efficient multiphase (MP) catalyst coating, consisting of Ba1−xCo0.7Fe0.2Nb0.1O3−δ (BCFN) and BaCO3, to enhance the ORR activity and durability of the state‐of‐the‐art lanthanum strontium cobalt ferrite (La0.6Sr0.4Co0.2Fe0.8O3−δ, LSCF) cathod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
42
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 68 publications
(51 citation statements)
references
References 70 publications
(116 reference statements)
1
42
0
Order By: Relevance
“…In our previous work, we developed a series of effective catalyst coatings on the surface of LSCF electrodes via a low-cost surface modification process. [18,[28][29][30] The coatings enhanced the ORR activity and durability of LSCF dramatically on oxygenion electrolyte-based fuel cells by increasing the surface oxygen exchange kinetics and inhibiting the surface Sr-segregation. While the enhancement of the reaction kinetics via surface modification has been extensively demonstrated for SOCs based on oxygen ion conductors, similar effects for R-PCECs have yet to be explored.…”
Section: An Efficient Bifunctional Air Electrode For Reversible Proto...mentioning
confidence: 99%
“…In our previous work, we developed a series of effective catalyst coatings on the surface of LSCF electrodes via a low-cost surface modification process. [18,[28][29][30] The coatings enhanced the ORR activity and durability of LSCF dramatically on oxygenion electrolyte-based fuel cells by increasing the surface oxygen exchange kinetics and inhibiting the surface Sr-segregation. While the enhancement of the reaction kinetics via surface modification has been extensively demonstrated for SOCs based on oxygen ion conductors, similar effects for R-PCECs have yet to be explored.…”
Section: An Efficient Bifunctional Air Electrode For Reversible Proto...mentioning
confidence: 99%
“…[23] It is suggested that cathodic polarization accelerated the Cr-poisoning by the fast Mn 2+ diffusion in LSM and the fast Sr diffusion in LSCF. [5,12] To improve the Cr tolerance of the cathode for an O-SOFC, a surface modification of electrodes with a rationally designed catalyst coating has been extensively adopted. [1,12,32,33] For example, Sr-free K 2 NiF 4 -type rare-earth nickelate catalyst coating, La 2 NiO 4+δ, [34] Nd 2 NiO 4+δ, and Pr 2 NiO 4+δ, [33] have been considered to be more Cr resistant.…”
Section: Introductionmentioning
confidence: 99%
“…[5,12] To improve the Cr tolerance of the cathode for an O-SOFC, a surface modification of electrodes with a rationally designed catalyst coating has been extensively adopted. [1,12,32,33] For example, Sr-free K 2 NiF 4 -type rare-earth nickelate catalyst coating, La 2 NiO 4+δ, [34] Nd 2 NiO 4+δ, and Pr 2 NiO 4+δ, [33] have been considered to be more Cr resistant. In addition, Chen et al reported the better ORR activity and Cr tolerance of LSCF by applying a conformal catalyst coating on the cathode such as BaO, La 0.8 Ca 0.2 FeO 3 , La 0.8 Ca 0.2 Ni 0.4 Fe 0.6 O 3 , Pr 0.75 Ca 0.2 MnO 3 , Pr 0.8 Ca 0.2 FeO 3 , and a hybrid catalyst of PrNi 0.5 Mn 0.5 O 3 and PrO x .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[3] Despite significant advances in recent years, [4,5] the performance of PCECs still suffers from limiting performance of the positive electrode-hereafter positrode-where the oxygen reduction reaction and oxygen evolution reaction-hereafter water oxygen redox reaction (WORX) for PCECs-take place. Generally, cathode materials for SOFCs, such as La 0.6 Sr 0.4 CoO 3-δ (LSC), [6] La 0.6 Sr 0.4 Co 0.2 Fe 0.8 O 3-δ (LSCF), [7] and Ba 0.5 Sr 0.5 Co 0.8 Fe 0.2 O 3-δ (BSCF) [8] are mixed electron hole and oxide ion conductors, with negligible proton conduction. If used in a PCEC, the WORX is therefore restricted to the three-phase boundary, where the electrolyte, positrode, and gas phase meet, resulting in large kinetic overpotential polarization.…”
mentioning
confidence: 99%